Improving crop disease resistance: lessons from research on Arabidopsis and tomato - Piquerez, Sophie J. M.; Harvey, Sarah E.; Beynon, Jim L.; Ntoukakis, Vardis (Frontiers in Plant Science, 2014)
One of the great challenges for food security in the 21st century is to improve yield stability through the development of disease-resistant crops. Crop research is often hindered by the lack of molecular tools, growth logistics, generation time and detailed genetic annotations, hence the power of model plant species. Our knowledge of plant immunity today has been largely shaped by the use of models, specifically through the use of mutants. We examine the importance of Arabidopsis and tomato as models in the study of plant immunity and how they help us in revealing a detailed and deep understanding of the various layers contributing to the immune system. Here we describe examples of how knowledge from models can be transferred to economically important crops resulting in new tools to enable and accelerate classical plant breeding. We will also discuss how models, and specifically transcriptomics and effectoromics approaches, have contributed to the identification of core components of the defence response which will be key to future engineering of durable and sustainable disease resistance in plants.